The Notion of Charisma Historicizing the Gift of God on Medieval Europe - Aurell Cardona, Jaume 1964- (2022)
This article analyzes the transformations in the concept of charisma since its original use by Paul in the first century up to its last post-Weberian derivations in the twenty-first century. It argues for the desirability of a return to its Pauline origins in order to apply it to historical realities, specifically those referring to medieval Europe. Its aim is to return the debate on charisma to the historical discipline, beyond the presentist orientation of the social sciences. Specifically, I highlight the dangers of ignoring the theological and spiritual origin of the whole discussion on charisma, and of the concept itself, to avoid antiquarian alienation or presentist solipsism.
Este artículo analiza las transformacio-nes del concepto de carisma desde su uso originalpor Pablo en el siglo I hasta sus últimas derivacionespostweberianas en el siglo XXI. Defiende la conve-niencia de volver a sus orígenes paulinos para aplicarlo a las realidades históricas, concretamente lasreferidas a la Europa medieval. Su objetivo es devolver el debate sobre el carisma a las disciplinas históricas y teológicas, más allá de la orientación presentista de las ciencias sociales. En concreto, destaco la distorsión que supone ignorar el origenteológico y espiritual de toda la discusión sobre elcarisma, y del propio concepto, para evitar la alie-nación anticuaria o el solipsismo presentista.
Keywords: Charisma; Saint Paul; Rudolf Sohm; Max Weber; Medieval Europe; Carisma; San Pablo; Rudolph Sohm; Max Weber; Europa medieval